The final exam - Daneshvari, Gitty (Daneshvari, Gitty. School of fear (New York, N.Y.), 2012)
When a reporter plans an exposé that could shut down the School of Fear, Garrison, Lulu, Madeleine, Theo, and Hyacinth seek help from Bishop Basmati, head of the nearby Contrary Conservatory, whose hyperactive, fearless, and extremely impulsive students soon overrun the school of Fearians.